Some Anatomical and Histological Features of the Brain in African Catfish (Clarias gariepinus) - El-Ghazali, Hanaa M.; Al-attar, Al-Sayed R.; Moselhy, Attia A.A. (Journal of Advanced Veterinary Research, 2023)
The purpose of the present study is to investigate the catfish brain morphology by gross anatomy, morphometric analysis in addition to light microscopy. A total of twenty African catfish (Clarias gariepinus), 30-80 cm long, with body mass 300-900gm, were used in this study. Anatomically, the brain of catfish is divided into five parts: telencephalon, mesencephalon, diencephalon, myelencephalon and metencephalon. The most prominent parts of catfish brain are optic tectum, telencephalon, and cerebellum. The morphometric analysis of the brain of catfish revealed a large optic tectum in the mesencephalon, whilst telencephalon and the cerebellum are of medium size. The brain occupies the caudal part of the cranial cavity. The brain is slightly elongated and narrow, slightly wider in the middle portion near the mesencephalon (optic tectum), eminentia granularis and the diencephalon. The telencephalon (cerebral hemispheres) single layer formed from various neuirons which are supported by neuroglia. The optic tectum consisted of five layers stratum marginale; stratum opticum; stratum album centrale; stratum griseum centrale and stratum periventriculare. The cerebellum histologically, formed from three different layers molecular, purkinje cell and inner granular layers. The optic nerve in catfish appeared large and thick.